2006
DOI: 10.1139/v06-169
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic hydrogenation of catechol on Rh–Al2O3 in different media — pH-Dependent reduction mechanism for intermediate formation

Abstract: The electrocatalytic hydrogenation of catechol was carried out in aqueous media in different pH ranges with Rh-Al 2 O 3 powder catalyst. The reactions were conducted in an H-cell used as a dynamic cell, with a reticulated vitreous carbon electrode in contact with the catalyst powder as the working electrode. It was shown that the final product is 1,2-cyclohexanediol (cis and trans isomers) and that several intermediates are detected depending on the pH of the solution. Different media, from pH 5 to 13, were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous research [12][13][14][15][16][17] on ECH of phenolic compounds has shown that large cathode surface areas are usually necessary to achieve high reaction rates. Electrodes made with pressed metallic powder particles have been successfully used, 18,19 but their mechanical strength is weak without addition of a binding material 20 and much surface area is lost in the powder pressing step.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [12][13][14][15][16][17] on ECH of phenolic compounds has shown that large cathode surface areas are usually necessary to achieve high reaction rates. Electrodes made with pressed metallic powder particles have been successfully used, 18,19 but their mechanical strength is weak without addition of a binding material 20 and much surface area is lost in the powder pressing step.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of the two isomers (cis and trans) of the cyclohexanediol suggests the presence of intermediate products. This particular aspect is the subject of another article from our group [18]. For temperatures between 25°C and 65°C, no significant effect on the ECH of catechol was observed under the conditions tested, as shown in Fig.…”
Section: Electrocatalytic Hydrogenation (Ech) Pathwaysmentioning
confidence: 83%
“…55,88 However, on Pd and Rh, phenol hydrogenates faster, and the hydrogenation of catechol proceeds faster toward the final products at pH 5 than at higher or lower pH values. 88,160,162 In stark contrast, the ECH of phenolic compounds on Raney Ni is enhanced as the pH becomes more basic. 147,148…”
Section: Electrocatalytic Hydrogenation Of Carbonyl Groupsmentioning
confidence: 99%
“…99,144,158 The contribution of Meńard and co-workers from the 1990s to the late 2010s must be highlighted because they mapped hydrogenation of phenol (and related organic compounds) on diverse catalysts (i.e., metal particles on carbon electrodes, carbon powders, and metal oxides) under several reaction conditions. 99,100,[144][145][146][160][161][162]173 ECH of phenolic compounds carried special momentum throughout the 2010s as low-temperature hydrogenation of biogenic feedstocks gained importance for the production of fuel and base chemicals. 19,339 Advances in the design of electrochemical reactors for organic transformations [152][153][154]175 have been paralleled by efforts to detail reaction networks and mechanisms and to explore the commonalities of electroand thermocatalysis.…”
Section: Electrocatalytic Hydrogenation Of Carbonyl Groupsmentioning
confidence: 99%
See 1 more Smart Citation